Analisis Etika Bisnis Islam Terhadap Praktek Jual-Beli Agen Di PT Ciomas Adisatwa Cabang Lampung Di Era Digital - Mia Oktavia; Hanif Hanif; Budimansyah Budimansyah (Management Studies and Entrepreneurship Journal (MSEJ), 2026)
This study aims to analyze the implementation of Islamic business ethics in the buying and selling practices carried out by agents at PT Ciomas Adisatwa, Lampung Branch, in the digital era. This research uses a qualitative approach with a case study method. Data were collected through in-depth interviews with three categories of informants: sales agents, branch managers, and customers. Data analysis was conducted thematically to explore the extent to which Islamic ethical principles are applied in digital trading practices. The results show that the trading practices at PT Ciomas Adisatwa Lampung Branch reflect Islamic business ethics, even though the term sharia is not explicitly used. Agents strive to be honest, fair, transparent, and responsible in every transaction, and they avoid elements of riba (usury) and gharar (uncertainty). Values such as honesty and ihsan (excellence in conduct) are evident in how they maintain good relationships with customers. However, in the digital era, agents face challenges such as intense business competition, the need for transparency in online transactions, data security, and the pressure of automation, which can be difficult to align with Islamic values. Another challenge is maintaining a human touch in digital services. To address these challenges, the company seeks to balance business efficiency with Islamic principles. They are improving digital systems to be more transparent, fair, and secure while ensuring services remain ethical and humane. Through these efforts, PT Ciomas Adisatwa aims to ensure that its trading practices continue to align with Islamic teachings, even in the digital age.